(untitled) (Research, Society and Development, 2023)
Oral health and general health are part of an individual’s well-being and quality of life, and when one is not favorable, it can compromise and aggravate the other. In hospitalized patients with poor oral hygiene, the condition can intensify and lengthen the days in the hospital bed. Elderly people, due to advancing age, have several systemic impairments, and become vulnerable to possible infections of hospital origin due to the inefficiency of the immune system. In this way, the oral cavity environment becomes a gateway for colonization if opportunistic microorganisms. The objective of this literature review is to highlight the importance of oral care in hospitalized geriatric patients. The searches were carried out in the database, PUBMED, SCIELO, BSV and LILACS, bringing together articles written in English or Portuguese, published in the years 2013 to 2023, using the descriptors: "Elderly", "Oral health", " Hospitalized’’ and ’’Intensive care units’’. According to the results obtained in the literature, it is concluded that it is essential to include the dentist within the multidisciplinary hospital team to prevent hospital infections that may worsen and aggravate the hospitalization of elderly people.